2019
DOI: 10.1097/md.0000000000017102
|View full text |Cite
|
Sign up to set email alerts
|

Combined hepatocellular-cholangiocarcinoma

Abstract: Combined hepatocellular-cholangiocarcinoma (CHCC) is a rare type of primary liver cancer (PLC). The aim of this study was to investigate the disease characteristics in CHCC patients and compare them with those in hepatocellular carcinoma (HCC) or intrahepatic cholangiocarcinoma (ICC).The perioperative and follow-up data of CHCC patients (n = 15), HCC patients (n = 577), and ICC patients (n = 61) were retrospectively analyzed, and the clinicopathological characteristics were compared among these 3 groups.In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 23 publications
4
28
1
Order By: Relevance
“…This median OS was higher than that reported in previous studies, which concluded that the median OS of patients with cHCC-CC ranged from 20 to 47 months [ 3 , 5 , 7 , 10 , 12 , 15 21 , 24 , 25 ]. Nevertheless, our study’s finding of significantly lower OS in the cHCC-CC group before PSM is consistent with the results of previous studies [ 2 , 5 ]. Notably, OS in the cHCC-CC group was not significantly different compared with the HCC or CC group after PSM.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This median OS was higher than that reported in previous studies, which concluded that the median OS of patients with cHCC-CC ranged from 20 to 47 months [ 3 , 5 , 7 , 10 , 12 , 15 21 , 24 , 25 ]. Nevertheless, our study’s finding of significantly lower OS in the cHCC-CC group before PSM is consistent with the results of previous studies [ 2 , 5 ]. Notably, OS in the cHCC-CC group was not significantly different compared with the HCC or CC group after PSM.…”
Section: Discussionsupporting
confidence: 93%
“…cHCC-CC is a rare type of PLC [ 1 , 2 ], and its incidence accounts for 0.4–14.2% of PLC [ 1 5 ]. Our study results indicated that there were 35 (7.0%) patients with cHCC-CC out of the 505 patients who underwent surgery for PLC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations